PROBLEMATIKA GURU DALAM MENGGUNAKAN MEDIA PEMBELAJARAN PADA MATA PELAJARAN IPS DI MADRASAH IBTIDAIYAH DARUSSALAM KOTA BENGKULU - Septi Dwi Putri; Desy Eka Citra (Indonesian Journal of Social Science Education (IJSSE), 2019)
Teachers problematic in using Learning Media in Social Science Education Subject at Madrasah Ibtidaiyah Darussalam Bengkulu City. This research aims to determine what problems are faced by teachers in using learning media and how teachers deal with these problems. This research was conducted in the Islamic Middle School Madrasah of the City of Bengkulu with the social studies teacher as a research subject. This research used descriptive qualitative method. Data collection technique used is in-defth interview and interactive model of Milles and Huberman for the data analysis, which consisted of three stages, namely data reduction, data display, and conclusion drawing. The results in the study are: 1) in using learning media, social studies teachers face several problems, namely problems in planning (making learning media), problems in using media (skills using learning media), and problems in choosing learning media - especially those that are suitable with material and learning methods; 2) in overcoming some problems with the use of instructional media, some of the things that social studies teachers do are like equipping themselves with knowledge about learning media, attending training, and training using various forms of learning media.